First Year International Students’ Experience in Universiti Malaysia Sabah - Bin Awang, Hasbullah; Wani Othman, Irma; Mohd Suki, Norazah (International Journal of Psychosocial Rehabilitation, 2019)
Internationalization is considered an efficient step to increase international students’ enrolment in Malaysia to fulfill the national aspiration of becoming a higher learning hub of excellence worldwide. This study explores the first-year experiences of international students by investigating the influencing factors on their decision to further study and their adaptation to the new environment at UMS. A qualitative research design using a case study that involved 20 international students who were selected using purposive sampling was carried out. A semistructured interview was used to gather information from these respondents. Based on the analysis of collected data, five themes were identified as the influencing factors on their decision to further study at UMS, which are: academic, culture, financial, university services, and social. These themes were further divided into sub-themes. Among them are the advantages and disadvantages of studying in UMS, education system differences, education program variety, educational course syllabus, and mastery of English language under the academic theme. The culture theme was divided into sub-themes like new experience, UMS culture, and external world view, while the financial theme is divided into financial resources from family and scholarship awards. University services are divided into two sub-themes: facilities and infrastructure and international office. Further to that, the social theme is represented by three subthemes comprising of parents and friends’ recommendations, social integration development, and the local community and college environment. Findings also presented the respondents’ view on the international students’ adaptation to the new environment. These were represented by eight themes, which are: mastery of the English language, group assignment, and instructional quality of academicians; cultural shock; adventure and gaining new experience; food access; satisfaction with facilities and infrastructure; and international student safety. Overall, feedback from the international students implied their satisfaction and positive first-year experience at UMS. Findings from this study are hoped to contribute to the Higher Education Ministry and UMS management in promoting greater enrolment and portraying UMS as the prime choice of study destination among international students.